FORTIFIKASI FE MINUMAN SUSU FERMENTASI KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) MENINGKATKAN KADAR HEMOGLOBIN DAN STATUS GIZI REMAJA PUTRI ANEMIA - Gunawan, Delima Citra Dewi; Dewi, Devillya Puspita; Astriana, Kuntari (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2021)
Background: Adolescent girls are particularly susceptible to iron deficiency anemia. Iron fortification is easier to accept than supplementation. Probiotics and prebiotics can increase mineral absorption and optimize nutrient absorption and have been shown to improve iron status and reduce anemia. Objectives: To determine effect of Fe fortification on Fermented Milk of Red Dragon Fruit (Hylocereus polyrhizus) peel on hemoglobin levels and nutritional status in anemic adolescent girlsMethods: This study was a randomized controlled trial with a pre and post test design with a total of 40 anemic adolescent girls. Subjects were divided into 2 groups, namely control group and treatment group. Treatment group was given a fermented red dragon fruit (Hylocereus polyrhizus) peel milk with iron fortification of 100 ml/day for 3 weeks. Blood sampling to determine hemoglobin levels and measurement of nutritional status before and after intervention.Results: Based on the results of statistical tests, there was no difference average on treatment group and control group hemoglobin levels before intervention with p-value=0.355. There was a difference average on treatment and control groups hemoglobin levels after intervention (p-value =0.000). There was a difference average on hemoglobin levels before and after treatment in the treatment group (p<0.001) but not in the control group (p-value=0.777). There was a difference average on treatment and control groups nutritional status both before and after intervention (p-value = 0.018 and p-value = 0.006). There was a difference average of nutritional status before and after intervention on treatment group (p<0.001), but not in control group (p-value = 0.165).Conclusion: Fe Fortification on Fermented Milk of Red Dragon Fruit (Hylocereus polyrhizus) Peel can increase Hb levels and nutritional status in treatment group but not in control group